Porous Matrix Stiffness Modulates Response to Targeted Therapy in Breast Carcinoma. Issue 34 (13th June 2016) - Liu, Cuiying; Li, Xiang; Hua, Wenda; Li, Jianjun; Han, Xinxiao; Ha, Qing; Feng, Jiantao; Liao, Fulong; Li, Dongguo; Han, Dong
Abstract : Porous matrix stiffness modulates response to targeted therapy . Poroelastic behavior within porous matrix may modulate the molecule events in cell‐matrix and cell–cell interaction like the complex formation of human epidermal growth factor receptor‐2 (HER2)‐Src‐α6β4 integrin, influencing the targeted therapy with lapatinib.